Six hundred thirty‐eight years of summer temperature variability over the Bhutanese Himalaya. Issue 8 (21st April 2015) - Krusic, P. J.; Cook, E. R.; Dukpa, D.; Putnam, A. E.; Rupper, S.; Schaefer, J.
Abstract High‐resolution tree ring reconstructions from the Himalaya provide essential context for assessing impacts of future climate change on regional water reserves and downstream agriculture. Here we evaluate a small network of tree ring chronologies from Bhutan to produce a 638 year summer temperature reconstruction, from 1376–2013 (Common Era) C.E. Relative to the 1950–2013 C.E. average summer temperature three prominent cold periods stand out, two in the midfifteenth century, and one in the late seventeenth century. The warmest period began in the first decade of the 21st century coinciding with the timing of general glacier recession in the eastern Himalaya that continues to the present. The Bhutan temperature reconstruction exhibits a significant correlation to known volcanic eruptions (p = 97%) and anomalously cold periods appear to align with solar irradiance minima in the fifteenth, late seventeenth, and early nineteenth centuries, implying a link between solar variability and decadal‐scale temperature variability.